Some particular aspects of certain type of probabilistic predator-prey model with experimenter-subject-controlled events and the fixed point method - Sintunavarat, Wutiphol; Turab, Ali (AIP conference proceedings, 2021)
This article focuses on a specific type of the predator-prey model under some experimenter-subject-controlled events. Our goal is to study predator animals’ behavior in these circumstances and establish a suitable mathematical model that encompasses all facets of these relationships. The Banach fixed point theorem is used to obtain the existence and uniqueness results of the suggested probabilistic model.